Working within professional boundaries in forensic mental health settings: an adult attachment perspective - Williams, Louise (2020)
Background - Boundary maintenance within any healthcare context is important, due to the potential adverse impact on patients. The criminogenic nature of forensic patients means that boundary maintenance is pertinent for the safety of patients, staff and members of the public alike. Individual precursors of boundary crossings are relatively well studied. However, interpersonal risk factors which may affect employee perceptions about the seriousness and acceptability of boundary crossing behaviour within forensic settings has received less research attention.